Unbalancing the Attentional Priority Map via Gaze-Contingent Displays Induces Neglect-Like Visual Exploration - Machner, Björn; Lencer, Marie C.; Möller, Lisa; von der Gablentz, Janina; Heide, Wolfgang; Helmchen, Christoph; Sprenger, Andreas (Frontiers in Human Neuroscience, 2020)
Selective spatial attention is a crucial cognitive process that guides us to the behaviorally relevant objects in a complex visual world by using exploratory eye movements. The spatial location of objects, their (bottom-up) saliency and (top-down) relevance are assumed to be encoded in one ‘attentional priority map’ in the brain, using different egocentric (eye-, head- and trunk-centered) spatial reference frames. In patients with hemispatial neglect, this map is supposed to be imbalanced, leading to a spatially biased exploration of the visual environment. As a proof of concept, we altered the visual saliency (and thereby attentional priority) of objects in a naturalistic scene along a left-right spatial gradient and investigated whether this can induce a bias in the exploratory eye movements of healthy humans (n=28; all right-handed; mean age: 23 years, range 19-48). We developed a computerized mask, using high-end ‘gaze-contingent display’ technology, that immediately and continuously reduced the saliency of objects on the left – ‘left’ with respect to the head (body-centered) and the current position on the retina (eye-centered). In both experimental conditions, task-free viewing and goal-driven visual search, this modification induced a mild but significant bias in visual exploration similar to hemispatial neglect. Accordingly, global eye movement parameters changed (reduced number and increased duration of fixations) and the spatial distribution of fixations indicated an attentional bias towards the right (rightward shift of first orienting, fixations favoring the scene’s outmost right over left). Our results support the concept of an attentional priority map in the brain as an interface between perception and behavior and as one pathophysiological ground of hemispatial neglect.